UP Movie (2009) as a Means of Improving Students' Understanding of Simple Present Tense - M. Diko Al Rasyid; Arfiyan Ridwan; Hendra Sudarso (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
This study aims to confirm a better understanding of simple present tense and , through a movie titled ‘Up’ set in a public school in a public Junior High School in East Java Province. This research uses a classroom action research. Based on the results of the study, the results of this study were very satisfying. This study succeeded in improving student present tense and tense throughout the film, supported by several other means, including word spelling correction, student motivation, and performing listening tasks. On this study, students’ understanding of the present tense can be improved. This can be seen in the increase in students understanding of simple present tense through the dialogue example during the first cycle. This research was successful in the effort to improve the students’ of simple present tense through up movie supported by some other actions such as correcting the word spelling, giving the students motivation, applying some listening and speaking activities. The increase of score between pre-test to post-test from 69.63 to 78.70 is the evidence that Up movie can improve students’ mastery of simple present tense through the communicative examples of movie dialogues and activities to assist pupils understand more in situational context.